"At my mother's knee" : the Psalms, the production of cultural memory and the cross generational transfer of the canon - Toit, J. S. du (Journal for Semitics, 2010)
In his 1998 SBL presidential address Patrick Miller reiterated the centrality of the emergence and maintenance of cultural memory achieved in Deuteronomy by means of the "regular rehearsal of the law in communal ritual and family life" and the "constant recollection of the story in its own preservation and rereading" as means of establishing identity for the religious collective in exile. Psalms, Miller argues, achieves the same by means of the anticipated regularity of the "spontaneous" recitation of songs. This article considers the integral status of Psalms as agency in the transfer of religious identity for modern religious collectives. It furthermore considers the central meaning of Psalms for the instruction of the religious collective in a family context, given its apparent absence in children's Bibles (the most common modern vehicles of instruction and representative of modern Bible interpretation in child acceptable format). In this context the configuration of story titles and the characterisation of the figure of David are foregrounded and contextualised by means of Miller's intimation of exilic ties between the function of Deuteronomy and Psalms within thetextual tradition.
paid
Keywords: University of the Free State